Workers' Birth Control Group (1927)
1927 1927 1920s 4 pages OBJECTS. Membership is open to men and women who are members of the Labour Party and its affiliated bodies or the Co-operative Guilds. Annual Subscription, 1/- The Objects of the Group are— (1) To strengthen public opinion among workers as to the importance of Birth Control in any scheme of social progress. (2) To bring within the reach of working people the best and most scientific information on Birth Control. (3) To bring pressure to bear through Parliament and otherwise on the Ministry of Health to recognise Birth Control as an essential part of Public Health work, and therefore to allow information to be given by the local Health Authorities at their Maternity and Child Welfare Centres. Meanwhile to help the promotion of Birth Control Clinics. The Group feel that the time has come for a vigorous Propaganda Campaign among the workers of the country who, while their need of Birth Control information is very great, are denied the opportunity afforded to the well-to-do to obtain it. The doctors at the Ministry of Health's Centres may not give this information, even to women whom they have certified as unfit for further child-bearing. The Group therefore urge the workers to join them and to promote Meetings all over the country, where the subject can be scientifically and practically discussed. 292/840/1/11